The Quay Brothers : into a metaphysical playroom - Buchan, Suzanne (Minneapolis, Minn. : University of Minnesota Press ; Bristol : University Presses Marketing [distributor], 2010)
Introduction -- Authentic trappers in metaphysical playrooms -- Palimpsests, fragments, vitalist affinities -- Traversing the esophagus -- Puppets and metaphysical machines -- Negotiating the labyrinth -- The secret scenario of soundscapes -- The animated frame and beyond -- These things never happen but are always.
Includes bibliographical references and index.
Formerly CIP.
boek
Keywords: Brothers Quay -- Criticism and interpretation